2018
DOI: 10.7150/ijms.25004
|View full text |Cite
|
Sign up to set email alerts
|

A human origin strain Lactobacillus acidophilus DDS-1 exhibits superior in vitro probiotic efficacy in comparison to plant or dairy origin probiotics

Abstract: Background: The health benefits of probiotics are well established and known to be strain-specific. However, the role of probiotics obtained from different origins and their efficacy largely remains unexplored. The aim of this study is to investigate the in vitro efficacy of probiotics from different origins.Methods: Probiotic strains utilized in this study include Lactobacillus acidophilus DDS-1 (human origin), Bifidobacterium animalis ssp. lactis UABla-12 (human origin), L. plantarum UALp-05 (plant origin) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 46 publications
(91 reference statements)
1
33
0
4
Order By: Relevance
“…M. smithii produces methane from the byproducts of bacterial fermentation and is present in up to 95% of fecal samples from human subjects [113]. Interestingly, M. smithii's abundance was found to be stable over time, even after major changes in diet [14,114]. In the human gut, methanogenic archaea may impact host metabolism, especially energy homeostasis and may contribute to obesity [79], by syntrophic interactions with gut bacteria, which increase short-chain fatty acid production and contribute to an excess of calories available to the host [115].…”
Section: Gut Archaeamentioning
confidence: 99%
See 1 more Smart Citation
“…M. smithii produces methane from the byproducts of bacterial fermentation and is present in up to 95% of fecal samples from human subjects [113]. Interestingly, M. smithii's abundance was found to be stable over time, even after major changes in diet [14,114]. In the human gut, methanogenic archaea may impact host metabolism, especially energy homeostasis and may contribute to obesity [79], by syntrophic interactions with gut bacteria, which increase short-chain fatty acid production and contribute to an excess of calories available to the host [115].…”
Section: Gut Archaeamentioning
confidence: 99%
“…For example, probiotics (single or multi-strained) are considered natural, safe, and beneficial modulators of the gut microbial composition, but their efficacy is strain-and dose-dependent and not all probiotics function against all disorders and diseases [154]. Fundamentally, to confer health benefits a probiotic needs to survive the acidic gastric digestion, other digestive enzymes, reach the intestine and colonize on the intestinal epithelium in good numbers [114]. In most of the probiotic trials, the vehicles for probiotic intake used are yoghurt, biscuits, bars, and capsules, per oral, which is not consistent across the studies and can potentially confound the outcomes [155].…”
Section: Modulation Of the Microbiome And Related Concernsmentioning
confidence: 99%
“…Probiyotik suşların her şeyden önce toksin üretmeyen ve vücuda alındıklarında sağlığa zarar vermeyen, yani GRAS (Generally Regarded As Safe) statüsündeki mikroorganizmalardan seçilmiş olması gerekmektedir. Ayrıca, bir mikroorganizmanın probiyotik olarak gıdada kullanılabilmesi için; tercihen insan orijinli olması, patojen olmaması, mide asidine ve safra tuzuna dayanıklı olması, bağırsak yüzeyine tutunabilmesi, gastrointestinal sistemde kısa da olsa yaşamını devam ettirebilmesi, antimikrobiyal karakterde bileşikler üretebilmesi, antibiyotik direncinin olmaması, bağışıklık sistemini uyarması, metabolik etkiler gösterebilmesi, (kolesterol asimilasyonu, laktaz aktivitesi, vitamin üretimi) ve teknolojik süreçlere dayanıklı olması beklenmektedir (Collins et al, 1998;Dunne et al, 2001;Önal-Darılmaz, 2010;Uymaz, 2010;Erem vd., 2013;Kechagia et al, 2013;Çomak-Göçer vd., 2016 (Vemuri et al, 2018).…”
Section: Sonunclassified
“…Bağırsak yüzeyine tutunmaya yönelik araştırmalarda, normal insan ince bağırsak villus hücrelerinin özelliklerine sahip olan Caco-2, HT-29, LS174T ve fetal I-407 hücre hatları, hücre kültürü çalışmalarında yaygın olarak kullanılmaktadır. Bununla birlikte adhezyonun incelenmesi dışında hücrelerin probiyotiklere gösterdiği reaksiyonu incelemek için de hücre kültürü kullanılmaktadır (Blum et al, 1999;Dunne et al, 2001;Brito et al, 2012;Argyri et al, 2013;Anonymous, 2018b;De Melo Pereira et al, 2018;Vemuri et al, 2018).…”
Section: Bağırsak Yüzeyine Tutunmaunclassified
“…However, the relationship between probiotics and gut microbiota in aging is unclear. Recently, we reported that the human origin strain Lactobacillus acidophilus DDS‐1 demonstrated superior probiotic traits in an in vitro setting . Taking this further, we evaluated the changes in microbial ecology, and immune and metabolite status in young and aging mice using DDS‐1.…”
Section: Modulation Of Gut Microbiota and Metabolic Profile After Supmentioning
confidence: 99%